Pedagogical Competence and Professionalism of Certified Elementary School Teachers: An Evaluation in Small Border Islands - Titin Kempa; Jems Sopacua; Jekriel Septory; Efilina Kissiya (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Kediri, 2026)
This study evaluates the implementation of pedagogical and professional competencies among certified elementary school teachers in Small Border Islands (Pulau-Pulau Kecil Perbatasan/PPKP), focusing on West Moa District, Southwest Maluku Regency, a geographically remote 3T (underdeveloped, frontier, and outermost) region facing serious educational challenges. The study adopted an evaluative approach using a descriptive qualitative design with quantified rubric-based scoring, grounded in Stake's Countenance Evaluation Model, in which competency achievement was benchmarked against the standards outlined in Indonesian Law Number 14 of 2005 on Teachers and Lecturers. Participants included five school principals and 18 certified elementary school teachers from five public primary schools in the district. Data were obtained through participatory observations, questionnaires, structured interviews, and document analysis, and were validated through triangulation of techniques and sources. Findings indicate that teachers demonstrate strong pedagogical competence (overall >92%), particularly in understanding learner characteristics (92.66%), communication with students (93.36%), and learning evaluation (94.66%). Professional competence also reached high levels (overall >90%), with the strongest result in lesson opening and closing (95.00%). In comparison, self-development scored lowest (89.90%) due to limited access to professional training networks in border areas. These results confirm that teacher certification has meaningfully strengthened pedagogical and professional capacities even under conditions of limited educational infrastructure. However, sustained, context-responsive professional development is essential to further enhance instructional quality in PPKP primary schools.